The Hexaco Personality Traits of Higher Achievers at the University Level - Jia, Ruofan; Bahoo, Rabia; Cai, Zhendong; Jahan, Musarrat (Frontiers in Psychology, 2022)
This study attempted to explore the personality traits of higher achievers at the university level. The core objective of this investigation was to illustrate the nature of personality traits of the higher achievers’ students. To study this phenomenon, a quantitative research approach was used. The students were chosen by using a purposive sampling technique and included 758 high achievers enrolled in various programs at the Chinese universities. Based on the Hexaco model of personality, a questionnaire was used to gather information from respondents as a research tool to examine the personality traits of position holders after an extensive review of the relevant literature. Tool validity was determined by following the face, content, construct (convergent and discriminant validity) validation process. This investigation concluded that honesty, emotionality, and openness to experience were very high among the higher achievers’ students. Only honesty in female higher achievers’ students was significantly high than male, remaining factors “extraversion, agreeableness, conscientiousness, and openness to experience” were significantly high among male higher achievers’ students. Moreover, the higher achievers of science group students were more extraversion, agreeableness, and conscientiousness than arts group students. However, higher achievers in hostels were more emotional and agreeableness than the day scholars. Overall step-wise regression analysis, indicated that agreeableness and extraversion factor has significant influence on higher achievers.